2008
DOI: 10.2105/ajph.2007.124610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hand Hygiene on Infectious Disease Risk in the Community Setting: A Meta-Analysis

Abstract: To quantify the effect of hand-hygiene interventions on rates of gastrointestinal and respiratory illnesses and to identify interventions that provide the greatest efficacy, we searched 4 electronic databases for hand-hygiene trials published from January 1960 through May 2007 and conducted meta-analyses to generate pooled rate ratios across interventions (N=30 studies). Improvements in hand hygiene resulted in reductions in gastrointestinal illness of 31% (95% confidence intervals [CI]=19%, 42%) and reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
547
3
21

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(606 citation statements)
references
References 62 publications
18
547
3
21
Order By: Relevance
“…Hand hygiene in nonhealthcare settings has reduced respiratory and gastrointestinal tract infections. 395,396 Hand hygiene opportunities for healthcare personnel, people with CF, and families are summarized in Table 7.…”
Section: Ivc Hand Hygienementioning
confidence: 99%
“…Hand hygiene in nonhealthcare settings has reduced respiratory and gastrointestinal tract infections. 395,396 Hand hygiene opportunities for healthcare personnel, people with CF, and families are summarized in Table 7.…”
Section: Ivc Hand Hygienementioning
confidence: 99%
“…Several low cost, efficient and effective interventions, such as providing running water within the kitchen area, improving water quality through household water treatment and washing hands using soap are acceptable interventions in most communities. They contribute effectively to the prevention of diarrhoeal diseases and the transmission of acute lower respiratory infection (ALRI) [7][8][9][10]. A recent systematic review provided evidence that hand washing with soap can reduce child diarrhoea by 48%, and the risk to acquire a diarrhoeal illness can be reduced by 17% and 36% through adequate household water treatments (HWT) and improved sanitation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although this method is adequate for rinsing o↵ dirt, it is ine↵ective at removing bacteria. As was found in previous studies, improper hand-hygiene might therefore be a significant source of coliforms in the community (Pickering et al , 2010b) which might lead to diarrhea (Aiello et al , 2008). The percentage of positive results are higher than has been found previously by Trevett et al (2005) who found a lower percentage 44% (n = 14) of contaminated hands than was found in this study, 96% (n = 48).…”
Section: Discussionsupporting
confidence: 45%